OFR-14-84 Improved Crowd Limit Switches And Greenhorn For Electric Shovels - Gary Choate (The National Institute for Occupational Safety and Health (NIOSH), 1983)
The work presented in this report represents the background activity which led to the fabrication and testing of a greenhorn and crowd limit switch system for electric shovels. The program began With a literature search and manufacturers product review to gather material as a basis for concept generation. Visits to three open pit mines provided information from operation and maintenance managers which was useful in preparing design concepts. These concepts were evaluated through laboratory tests and engineering analysis to select a final design concept. The resultant greenhorn is four separate shock absorbing pads each enclosed in a housing which bolts to the end of a dipper handle adaptor. The plungers impact against stops mounted to the saddle block. The crowd limit control is a nonmechanical device which senses the location of the dipper and makes appropriate commands to the crowd motor to insure against impacting the greenhorns. The electronic crowd limit control is redundant and indicates malfunction modes. The greenhorn prevents shovel damage in the unlikely event of impact.